Intracellular Localization of Phosphatidylcholine and Phosphatidylethanolamine Synthesis in Cotyledons of Cotton Seedlings - Chapman, Kent D. (1991)
Subfractionation of clarified cotyledon homogenates of cotton (Gossypium hirsutum L.) seedlings on sucrose gradients revealed a single coincident peak of cholinephosphotransferase (EC 2.7.8.2) (CPT) and ethanolaminephosphotransferase (EC 2.7.8.1) (EPT) activities, which equilibrated with the main peak of Antimycin A-insensitive NADH:cytochrome c reductase (CCR) activity. The small percentage of CPT and EPT activities (less than 5% of the total) in glyoxysome-enriched pellets equilibrated with cytochrome c oxidase activity, not with catalase activity. Preincubation of microsomes (containing 83% of total CPT and EPT activities) in 0.2 millimolar MgCl(2) followed by subfractionation on sucrose gradients resulted in peak CPT and EPT activities equilibrating with peak CCR activity at 24% (w/w) sucrose. Preincubation of microsomes with (14)C-CDPcholine (or (14)C-CDPethanolamine) resulted in synthesis and incorporation of (14)C-phosphatidylcholine (PC) (or (14)C-phosphatidylethanolamine, PE) into membranes at the same density. Increasing the Mg(2+) concentration to 2.0 millimolar facilitated binding of ribosomes and caused a concomitant shift in density (to 34% w/w sucrose) of peak CPT, EPT, and CCR activities. Under these conditions, newly synthesized and incorporated (14)C-PC (or PE) was recovered in these membranes. Transmission electron microscopy of this fraction confirmed binding of ribosomes to membranes. Radiolabeling in vivo of cotyledons with [methyl-(14)C] choline chloride or [1,2 ethanolamine-(14)C] ethanolamine hydrochloride resulted in a linear incorporation of radiolabel into PC or PE in a time dependent manner. Subfractionation of homogenates of radiolabeled cotyledons on sucrose gradients showed that membranes sedimenting at 24% (w/w) sucrose (ER) contained the majority of radiolabeled PC and PE with a minor peak at 40% (w/w) sucrose (mitochondria), but no radioactive PC or PE was recovered in glyoxysomes. These results indicate that ER in cotyledons of germinated cotton seedlings is the primary subcellular site of PC and PE synthesis. This is similar to the situation in endosperm tissue but distinctly different from root and hypocotyl tissue where Golgi are a major subcellular site of PC and PE synthesis.